An investigation on machinability of nitronic 50 in dry environment using uncoated WC-Co tool inserts. (2022) - Banerjee, Ayan; Maity, Kalipada
Abstract: A variety of nitrogen strengthened austenitic stainless steels namely Nitronic 50 is a very useful alloy for marine industry finding its application in the form of drive shafts, pump shafts, valve fittings, pressure vessels, fasteners, sucker rods for oil rigs etc. Studies regarding machinability of this alloy is almost nil and hence it demands a proper investigation of the machining characteristics of this alloy. In the current work, turning has been performed on Nitronic 50 under dry environmental condition using uncoated tungsten carbide inserts and responses in the form of magnitude of tool-tip temperature, surface roughness, cutting force and tool wear were studied. Results showed that employment of higher cutting speed (170 m/min) resulted in enhanced cutting forces, rapid tool wear and BUE development while lower cutting speed promoted higher surface roughness. Use of cutting speed at the intermediate level of 130 m/min showed lesser tool wear, acceptable surface roughness and maintained an overall productivity.